Postmodern Principles in Integrated Teaching of Foreign Languages and Fine Arts to Primary Learners in the New Ukrainian School - Фрумкіна, Арина Леонівна; Фрумкіна, А. Л.; Фрумкина, Арина Леоновна; Frumkina, Aryna L. (LUMEN Publishing House, 2021)
The article deals with the issue of integrated teaching of foreign languages and fine arts to primary learners in the New Ukrainian school that seeks to overcome postcolonial and modernist traditions of education and gradually implements postmodern education principles. In this regard, the article highlights the use of such postmodernist trends as simulation, free interpretation, and establishment of personal associative connections in integrated teaching of foreign languages and fine arts. Such a need is based on the hypothesis that primary learners are extremely sensitive to the above-mentioned trends and can enrich their vocabulary via consecutive study-visualization of foreign language words and their denotations. Research methods include theoretical analysis of relevant sources, pedagogical modelling of stages, special methods of integrated teaching of foreign languages and fine arts, prognostic methods. The article presents the step-by-step process of integrated teaching of foreign language and fine arts. It proves that integrative teaching in primary school thematically and methodically coincides with the three-stage process of acquiring the basics of foreign languages and fine arts. Besides, the article contains practical recommendations on the organization of integrated teaching of foreign languages and fine arts. The international relevance of the article lies in projecting the postmodern education principles on didactic realities of developing countries that need to learn the experience of educational transformation based on Ukraine’s example, as well as in implementing these principles in integrated teaching of foreign languages and fine arts.

У статті розглядається питання інтегрованого навчання іноземних мов та образотворчого мистецтва учнів початкової школи в Новій українській школі, яка прагне подолати постколоніальні та модерністські традиції освіти та поступово реалізує постмодерністські принципи освіти. У зв’язку з цим у статті висвітлюється використання таких постмодерністських напрямків, як моделювання, вільна інтерпретація, встановлення особистісних асоціативних зв’язків у інтегрованому навчанні іноземних мов та образотворчого мистецтва. Така потреба ґрунтується на гіпотезі, що учні початкової школи надзвичайно чутливі до вищезгаданих тенденцій і можуть збагачувати свій словниковий запас шляхом послідовного вивчення-візуалізації іншомовних слів та їхніх денотатів. Методи дослідження включають теоретичний аналіз відповідних джерел, педагогічне моделювання етапів, спеціальні методи інтегрованого навчання іноземних мов і образотворчого мистецтва, прогностичні методи. У статті представлено поетапний процес інтегрованого навчання іноземної мови та образотворчого мистецтва. Доведено, що інтегративне навчання в початковій школі тематично та методично збігається з триступеневим процесом оволодіння основами іноземних мов та образотворчого мистецтва. Крім того, стаття містить практичні рекомендації щодо організації інтегрованого навчання іноземних мов та образотворчого мистецтва. Міжнародна актуальність статті полягає в проектуванні принципів постмодерної освіти на дидактичні реалії країн, що розвиваються, які потребують засвоєння досвіду освітньої трансформації на прикладі України, а також у реалізації цих принципів у інтегрованому навчанні іноземних мов та образотворчого мистецтва.
Frumkina A. Postmodern Principles in Integrated Teaching of Foreign Languages and Fine Arts to Primary Learners in the New Ukrainian School / A. Frumkina // Revista Romaneasca pentru Educatie Multidimensionala. Vol. 13. - Iss. 4. - LUMEN Publishing House, 2021. - Р. 579-594.
Keywords: foreign languages; fine arts; integrated teaching; postmodern education; primary learners; primary school teachers; іноземні мови; образотворче мистецтво; інтегроване навчання; постмодерна освіта; учні початкової школи; вчителі початкової школи; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education